Tindak Tutur Ekspresif pada Channel Youtube Hujan Tanda Tanya dalam Konten Edukasi tentang Pengembangan Diri dan Pembelajaran - Arrahma Qonita Al Arifin; Rafa Naufal Anoka; Alya Nur Lailia Rahmah; Agna Septia Ramadhani; Sabrina Yasmin Paramita; Asep Purwo Yudi Utomo; Isnarto Isnarto (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Language is the primary tool of communication, serving to convey human ideas, feelings, and thoughts in social interaction. One important study in pragmatics is speech acts, particularly expressive speech acts, which express the speaker's psychological state thru utterances. This research focuses on analyzing the expressive speech acts found in the YouTube channel Hujan Tanda Tanya, an educational channel managed by Rousyan Fikri, also known as Hutata. The objectives of this research are (1) to describe the types of expressive speech acts found on the Hujan Tanda Tanya YouTube channel and (2) to identify the forms of these expressive speech acts. This research uses a descriptive qualitative method with content analysis techniques applied to three videos uploaded on that channel. The research results show that there are five forms of expressive speech acts, namely complaining, expressing gratitude, praising, and supporting, with a total of 25 utterance data. The most dominant form of expressive speech act is praise, as the content in this channel provides a lot of positive encouragement to its viewers. This research is beneficial for enriching the study of pragmatics, particularly in understanding the application of expressive speech acts in digital media, and serves as a reference for discourse analysis on other educational platforms.